The Correlation between Subolesin-Reactive Epitopes and Vaccine Efficacy - Contreras, Marinela; Kasaija, Paul D.; Kabi, Fredrick; Mugerwa, Swidiq; De la Fuente, José (Vaccines, 2022)
Vaccination is an environmentally-friendly alternative for tick control. The tick antigen Subolesin (SUB) has shown protection in vaccines for the control of multiple tick species in cattle. Additionally, recent approaches in quantum vaccinomics have predicted SUB-protective epitopes and the peptide sequences involved in protein–protein interactions in this tick antigen. Therefore, the identification of B-cell–reactive epitopes by epitope mapping using a SUB peptide array could be essential as a novel strategy for vaccine development. Subolesin can be used as a model to evaluate the effectiveness of these approaches for the identification of protective epitopes related to vaccine protection and efficacy. In this study, the mapping of B-cell linear epitopes of SUB from three different tick species common in Uganda (Rhipicephalus appendiculatus, R. decoloratus, and Amblyomma variegatum) was conducted using serum samples from two cattle breeds immunized with SUB-based vaccines. The results showed that in cattle immunized with SUB from R. appendiculatus (SUBra) all the reactive peptides (Z-score > 2) recognized by IgG were also significant (Z-ratio > 1.96) when compared to the control group. Additionally, some of the reactive peptides recognized by IgG from the control group were also recognized in SUB cocktail–immunized groups. As a significant result, cattle groups that showed the highest vaccine efficacy were Bos indicus immunized with a SUB cocktail (92%), and crossbred cattle were immunized with SUBra (90%) against R. appendiculatus ticks; the IgG from these groups recognized overlapping epitopes from the peptide SPTGLSPGLSPVRDQPLFTFRQVGLICERMMKERESQIRDEYDHVLSAKLAEQYDTFVKFTYDQKRFEGATPSYLS (Z-ratio > 1.96), which partially corresponded to a Q38 peptide and the SUB protein interaction domain. These identified epitopes could be related to the protection and efficacy of the SUB-based vaccines, and new chimeras containing these protective epitopes could be designed using this new approach.
Keywords: Subolesin; Q38; Epitope; Vaccine; Cattle; Quantum vaccinomics; Tick